The stock condition, abundance dynamics and the prospects of fishery for the Baltic salmon in the rivers of the Latvian SSR - Evtyukhova, B.K. (Baltijskij Nauchno-issledovatelskij Institut Rybnogo Khozyajstva; "Zvaigzne", 1968)
The stock condition of the Baltic salmon Salmo salar in the years 1956-1966 and its year-class abundances in the period 1951-1964 are considered. The abundance dynamics of the year-classes in the Daugava River (Latvia) is analyzed. The analysis of the dependence of the year-class abundance on various factors indicates that the food basis of the salmon young stages in the Daugava limits their abundance. The dependence of the year-class abundance on the factors influencing it allowed the composition of forecasts on the possible salmon catches 1-4 years in advance. In the article data on the impact of foreign fishery on the Latvian salmon stock are presented. Published Not Known